MONTHLY VARIATION OF TOTAL EARTHWORM POPULATION IN A SUB-TROPICAL FOREST ECOSYSTEM OF MOKOKCHUNG DISTRICT IN NAGALAND - LILONGCHEM THYUG; L. N. KAKATI; VETHSELO DOULO; LIRIKUM; RUOKUOVIKHO DOMINIC; RUOKUOVIKHO DOMINIC (The Bioscan, 2019)
Amynthas corticis, Amynthas sp.1, Perionyx sp., Drawida sp., Eutyphoeus festivus, Eutyphoeus sp.no.1 and Eutyphoeus marmoreus belonging to three families Megascolecidae, Moniligastridae and Octochaetidae were recorded. However, Amynthas sp.1 was recorded only in the forest ecosystem. The total earthworm density at 0- 10 cm in the natural forest ecosystem was maximum in the month of September (88 m - ²) and minimum in December (22 m - ²). In the fallow ecosystem, the density fluctuation indicated two peak months i.e. June (43.98 m - ²) and September (64.76 m - ²). While, in the plantation ecosystem, it recorded maximum in the month of September (57.43 m - ²) and minimum in December (13.43 m - ²) at 0-10 cm layer. Among the three sites, reserve forest recorded the highest annual earthworm population density (609.68 Nos. m - ²) followed by plantation (386.1 Nos. mÉ²) and fallow (356.56 Nos. m - ²) respectively. Moisture content, Soil temperature and Nitrogen content showed high positive significant relationship in the reserve forest (r=0.39, P<0.05; r=0.49.P<0.01; r=0.35, <P0.05), fallow (r=.0.68, P<0.01; r=0.79, P<0.01; r=0.40, P<0.05) and plantation (r=0.39, P<0.05; r=0.51, P<0.01; r=0.37, P<0.05) sites respectively.